A critical review of African green building research. Issue 6 (18th August 2022) - Mushi, Frank Victor; Nguluma, Huba; Kihila, Jacob
ABSTRACT: A key component of green building diffusion is green building research. Globally, sustainable and green building research is advancing. However, there exists scanty research output on green building diffusion at the regional level. This paper presents a critical review of the existing body of knowledge on green building research, focusing on the African context. The major areas covered include green building research study trends, common topics and cross-country contributions to the body of knowledge. The study highlights the social aspects and economic issues of green building adoption and implementation and tailored green building rating tools. The study deployed a triple bottom line outlay in presenting the findings derived from extant research. In particular, the study uncovered that the coverage of African green building research is similar to that at the global level. Moreover, although social and economic factors influencing green buildings' implementation were noted, environment-oriented research remained dominant. The study recommends that forthcoming scholars need to advance research knowledge on the identification of cost–benefit evidence of adopting green buildings, application of information communication technology in green building research and theoretical insights underpinning green building diffusion.